The Role of the Notary in Making the Deed of Establishment of Savings and Loans Cooperative - Dimas, M. (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
Cooperative legal entities in practice cannot be denied that these legal entities have cases that can harm the Cooperative in question, where the problem lies in the result of committing a form of negligence and even intentional perpetration by the founders of the Cooperative. On a scientific basis, writing is motivated to carry out a scientific study in the form of systematic and fundamental research with the title